AB0363 Assymetric Dimethylarginine is Associated with Cumulative Inflammatory Burden in Rheumatoid Arthritis. (10th June 2014) - Dimitroulas, T.; Sandoo, A.; Hodson, J.; Smith, J.; Douglas, K.; Kitas, G.
Abstract : Background: Rheumatoid arthritis (RA) is associated with premature cardiovascular (CV) morbidity and mortality. Inflammatory processes in the rheumatoid synovium and atherosclerotic plaques are remarkably similar, suggesting that RA disease-related inflammation may potentiate the effect of traditional CV risk factors leading to excess CV risk. However, the relationship between atherosclerosis and systemic inflammation in RA remains controversial. Assymetric dimethylarginine (ADMA) – an endogenous inhibitor of nitric oxide synthase - has emerged as a novel surrogate marker of endothelial dysfunction and CVD risk. ADMA levels are elevated in patients with RA compared to controls in several studies. Objectives: The aim of the present study was to investigate the associations of cumulative inflammatory burden (assessed by serial measurements of inflammatory markers) and classical CV disease risk factors with ADMA, in a large prospective cohort of patients with established RA. Methods: 201 RA patients [155 females median age 67 (59 – 73)] were assessed at baseline (2006) for presence of classical CVD risk factors and determination of systemic inflammation by C-reactive protein (CRP) and erythrocyte sedimentation rate (ESR). At follow-up (2012) ADMA levels were measured by ELISA. A quarterly measurement of CRP and ESR for each year the patient was in the study was used to average areas under the curve (AAUC) for ESR and CRP. Results: Regression analysis revealed that baseline ESR in 2006 and the AAUC of ESR and CRP all had significant positive relationships with current ADMA (p=0.004, <0.001, 0.002 respectively). Baseline CRP in 2006 was not a significant predictor of ADMA (p=0.093), although this relationship was in the same direction as the other factors. The analysis remained the same when adjusting for classical CV disease risk factors. Conclusions: Cumulative inflammatory burden is positively related to ADMA levels, suggesting a potential pathogenic mechanism through which chronic systemic inflammation exerts deleterious effects on nitric oxide metabolism and endothelial homeostasis. This association is independent of classical CV disease risk factors. References: Dimitriulas T, Sandoo A, Kitas GD. Assymetric dimethylarginine as a surrogate marker of endothelial dysfunction and cardiovascular risk in patients with systemic rheumatic diseases. Int J Mol Sci 2012;13:12315-35 Sandoo A, Dimitroulas T, van Zanten JJ et al. Lack of association between assymartic dimethylarginine and in vivo macrovascular and microvascular endothelial dysfunction in patients with rheumatoid arthritis. Clin Exp Rheumatol 2012;30;388-96. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.1772